Salient Features of the Constitutions of Nepal and India: A Comparative Observation - Gautam, Dilli Raj (KMC Research Journal, 2019)
While comparing the Constitution of Nepal 2015 and the Constitution of India 1950 the paper comparatively analyses the major issues such as citizenship, inclusiveness, fundamental rights and independence of judiciary. Both constitutions are committed to socialism based on democratic norms and values, including people’s competitive multiparty democratic system of governance, civil liberties, fundamental rights, federal republic, secularism, adult franchise, periodic elections, full freedom of the press, and independent, impartial, competent and free judiciary and concept of the rule of law. This qualitative research article observes the salient features of the constitution of Nepal and India in descriptive and analytical order with comparative methodology.